Pengaruh Independensi Dan Komitmen Organisasi Terhadap Kualitas Audit (Studi pada Kantor Akuntan Publik di Bandar Lampung, Bandung, dan Jakarta) - Riswan RISWAN (Universitas Bandar Lampung (UBL), 2012)
Problems faced by public accountants today is the issue of deterioration of ethical standards and a crisis of confidence in auditing that will have an impact on the quality of the companys financial statement audit. Any deterioration of ethical standards and a crisis of confidence in public accounting is influenced by several factors such as the level of auditor independence and commitment in conducting the audit.This research aims to obtain the empirical evidences whether independence and organizational commitment partially give the positive influences to audit quality. The research is conducted to the independent auditor from various Public Accountant Offices by spreading closed questioners to the chosen location as the sample. The sampling technique used sampling area, then the data were analysed using Structural Equation Modelling that based on covariance structure, called Linear Structural Relations (LISREL). This modeling technique consists of the measurement model and structural model. Measurement model used to measure the dimensions that form a factor or latent variable, whereas the structural model describes the influence and relations between constructs or latent variables. The researches result concludes that independence and organization commitment partially give the positive influences and significant to audit quality.